Consumer Perceptions of Generation Z of Go-Ride Service Product Based on Marketing Mix Concept - Brahmana, Putri Angelina; Amina, Amanda Keisya; Suciati, Pijar; Maulidiyanti, Mareta (Universitas Nusa Cendana, 2024)
This study aims to explore Generation Z's perceptions of Go-Ride services and analyze the application of the 7Ps marketing mix concept within Go-Ride services offered by the Go-Jek application. To achieve this objective, a mixed research methodology was employed. Quantitative data were gathered through a survey conducted among Universitas Indonesia (UI) students aged 15-24 from November 28, 2022, to December 21, 2022, using Google Forms. Qualitative data were obtained through interviews. Our research findings reveal that Go-Ride services play a significant role in providing fast and economical mobility for Generation Z. Additionally, it unveils varying perceptions within this demographic regarding Go-Ride services, shedding light on the nuances of their preferences and expectations. This study contributes to the existing body of knowledge by offering insights into the distinctive perspectives of Generation Z regarding Go-Ride services. By applying the 7Ps marketing mix concept, it provides a deeper understanding of the marketing strategies and tactics utilized in these services. Furthermore, the mixed research approach employed in this study enhances the comprehensiveness of the findings, making it a valuable resource for addressing real-world challenges within the Go-Jek community.